Beyond 50:50 of Matrimonial Asset: Applying the Contra Legem Principle in Marital Property Division in Indonesia - Tanjung, Afriansyah; Lubsi Tuqo Romadhan, Moh.; Khoirul Ummah, Maela (Recital Review, 2025)
This paper investigates the legal and ethical implications of deviating from the equal (50:50) distribution of marital property in Indonesian divorce cases, particularly when one spouse acts in bad faith. While Indonesian law—namely Article 35 of the Marriage Law and Article 97 of the Compilation of Islamic Law—generally upholds equal division of joint property, this study highlights how courts may apply the contra legem principle to achieve substantive justice. Using a normative legal method, the research examines regulations and judicial discretion in reallocating marital assets when faced with evidence of misconduct, unequal contributions, or financial manipulation. The study draws from comparative legal systems and landmark court decisions to illustrate how contra legem serves not as a defiance of law, but as a mechanism to protect vulnerable spouses and promote fairness. It concludes that flexible, contribution-based distribution, supported by judicial transparency and evidentiary standards, better reflects the realities of modern marriages and ensures just outcomes within Indonesia’s dual legal framework.